Bis(isonicotinamide-κN)silver(I) trifluoromethanesulfonate acetonitrile disolvate - Rafael A. Adrian (International Union of Crystallography, 2021)
The central AgI atom of the title salt, [Ag(INAM)2](CF3SO3)·2CH3CN, where INAM is isonicotinamide (C6H6N2O), is twofold coordinated by the pyridine N atoms of two isonicotinamide ligands creating a slightly distorted linear molecular geometry. The formation of polymeric chains {[Ag(INAM)2]+}n, held together by discrete hydrogen bonds through the amide group of the INAM ligand leaves voids for non-coordinating acetonitrile molecules that interact the silver metal center via regium bonds.